(untitled) (Swiss Medical Weekly, 2025)
For more than 20 years, Switzerland has had a national binding set of learning objectives to guide medical education at universities. The learning expectations, compiled in the Principal Relevant Objectives and Framework for Integrative Learning and Education in Switzerland (PROFILES), were revised in 2023. The purpose of this article is to describe the revision process and highlight the changes and updates in PROFILES 2. The new document consists of three interrelated and interdependent chapters: the Competencies and Roles (CRs), the Entrustable Professional Activities (EPAs) and the Situations as Starting Points (SSPs). The CRs are based on the CanMEDS roles, which describe the personal attributes and competencies of the graduate. EPAs define what activities the graduate is expected to perform on the first day of residency. SSPs represent situations in which the professional activities are expected to be performed. In terms of content, three new areas of focus have been added: planetary health; diversity, equity and inclusion (DEI); and digitalisation. The revised PROFILES reflects current best practice in medical education and will help to ensure that the needs of future generations of doctors and society are met.